Unpacking livelihood challenges and opportunities in energy crop cultivation: perspectives on Jatropha curcas projects in Mali. Issue 4 (28th October 2013) - Favretto, Nicola; Stringer, Lindsay C; Dougill, Andrew J
<x xml:space="preserve">Abstract</x> This study contributes to global debates on biofuels and rural development, providing insights into the role of Jatropha curcas L. (Jatropha) in addressing global poverty and promoting sustainable energy. Jatropha energy crop investments have proliferated as a means to substitute imported oil, foster rural development and reduce poverty. This paper presents new mixed‐method assessments of the potential for, and initial impacts of, Jatropha projects that aim to improve livelihoods and energy security in rural Mali, a leading proponent of Jatropha cultivation. Factors affecting the socio‐economic and environmental vulnerabilities of smallholder farmers are assessed and capital assets available for different livelihood strategies are identified and evaluated. Comparative analysis of information gathered through participatory methods allows evaluation of the role played by Jatropha cultivation in the determination of different livelihood outcomes. Data show that households involved with NGO or private sector activities linked to Jatropha can gain financial capital from the sale of Jatropha seeds and soap. Findings also show that small‐scale cultivation does not threaten food security. When grown on a small scale as a living fence, Jatropha demarcates property, and reduces land tenure conflicts and soil erosion. Projects focusing on Jatropha use for rural electrification offer potential to improve energy access. However, current supplies of Jatropha oil remain insufficient for these benefits to materialise. On‐the‐ground challenges were identified, along with opportunities to better link policies to local‐level practices.